2017
DOI: 10.1371/journal.pone.0178888
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and phenotypic characterisation of fluoroquinolone resistance mechanisms in Enterobacteriaceae in Durban, South Africa

Abstract: Resistance to fluoroquinolones (FQ) is being increasingly reported and found to be mediated by efflux pumps, plasmid-mediated quinolone resistance genes (PMQR) and mutations in gyrA, gyrB, parC and parE. However, studies reporting on FQ resistance mechanisms (FQRM), particularly in Africa, are focused mostly on Salmonella. This study used a whole-genome-based approach to describe FQRM in forty-eight clinical Enterobacteriaceae isolates comprising of Klebsiella pneumoniae (n = 21), Serratia marcescens (n = 12),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 27 publications
7
59
3
Order By: Relevance
“…Only three observational studies reported on the presence of all currently known resistance determinants. 33,97,98 Since mutations in both acrR and marR genes were shown to result in no to low fold changes in ciprofloxacin MIC, we added five observational studies that fulfilled all inclusion and exclusion criteria except testing for the presence of mutations in acrR and marR genes, in a secondary analysis. Thus, eight observational studies published between 2012 and 2018 were included, contributing data on a total of 238 strains (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Only three observational studies reported on the presence of all currently known resistance determinants. 33,97,98 Since mutations in both acrR and marR genes were shown to result in no to low fold changes in ciprofloxacin MIC, we added five observational studies that fulfilled all inclusion and exclusion criteria except testing for the presence of mutations in acrR and marR genes, in a secondary analysis. Thus, eight observational studies published between 2012 and 2018 were included, contributing data on a total of 238 strains (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Fluoroquinolone resistance mechanisms were further investigated by determining mutations in DNA gyrase ( gyrA ) and topoisomerase IV ( parC ) using fluoroquinolone‐susceptible P. rettgeri DSM 1131 (accession no. ACCI00000000) as the reference/wild‐type strain to call single‐nucleotide polymorphisms (SNPs) with tBLASTn . The same process was followed to determine the presence of colistin resistance‐conferring mutations in mgrB, pmrAB , and phoPQ .…”
Section: Methodsmentioning
confidence: 99%
“…ACCI00000000) as the reference/wild-type strain to call single-nucleotide polymorphisms (SNPs) with tBLASTn. 27 The same process was followed to determine the presence of colistin resistance-conferring mutations in mgrB, pmrAB, and phoPQ.…”
Section: Resistome Annotation Virulome Predictions and Identificatimentioning
confidence: 99%
“…The oqxA gene appears to be rare among isolates identified in Denmark, Sweden, and South Korea. Recent reports suggest that it is common in South Africa and potentially other parts of the continent but there are few studies performed in sub-Saharan Africa have sought these genes (5,(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%